PARENTAL AND LEARNER VOICES IN SCHOOL FINANCIAL MANAGEMENT: INSIGHTS FROM A RURAL KWAZULU-NATAL CASE STUDY - Zakhele Dennis Nzuza; Fahrus Zaman Fadhly (Indonesian Journal of Learning and Instruction, 2025)
Democratic school governance in South Africa mandates parental and learner participation in financial management through School Governing Bodies (SGBs). However, effective involvement in rural schools remains poorly understood. This study examined the nature and challenges of parent and learner participation in school financial management at a rural school in KwaZulu-Natal’s Umzinyathi District. A qualitative case study was employed, using semi-structured interviews with eight SGB members at a selected secondary school. Data were analysed thematically. Key challenges include unclear roles and responsibilities, insufficient financial skills among SGB members, a lack of formal financial policy guidelines, poor communication, and the exclusion of parents and learners from meaningful decision-making, leading to frustration and disengagement. Participation is largely symbolic rather than substantive, undermining accountability and transparent governance. To enhance financial governance, targeted capacity-building programmes, the development of clear school-based financial policies, and inclusive communication strategies are urgently needed to empower all SGB stakeholders.